Bilateral true vocal fold avulsion following trampoline accident: A case report - Allison Epstein; Alexandra Welschmeyer; Temitope Adeyeni; Jamil Hayden; Matthew Gropler; Jay Shah; Nelson Scott Howard (JEM Reports)
Background: Vocal cord avulsion is a rare and potentially devastating injury which may result from blunt laryngotracheal trauma. While there are cases of unilateral vocal cord avulsion, we present a pediatric patient with bilateral vocal cord avulsion from blunt trauma to the anterior neck following a trampoline accident. Case report: This 10-year-old female presented with dysphonia and dysphagia and was found to have bilateral vocal cord avulsion effecting the superior vocal fold with a noticeable height mismatch and exposed cartilage seen only on diagnostic direct laryngoscopy, corresponding to a Schaeffer Grade 3 laryngeal injury. Distal chip laryngoscopy was not as useful in providing a comprehensive examination of the patient due to muscle tension with arytenoid prolapse. Primary endoscopic repair was performed with subsequent improved vocal cord position, voice quality, and tolerance of oral intake. Why should an emergency physician be aware of this?: Laryngeal trauma in children is rare, and early detection is critical to optimize long term outcomes. To date, no universal protocol for diagnosis and management of these injuries in the pediatric population exists. A low index of suspicion of endolaryngeal injury must be maintained for children with these injuries given their smaller airway diameter and increased propensity to develop acute airway compromise in the absence of obvious warning signs or symptoms. We highlight our endoscopic repair technique and excellent postoperative course with improvements in voice, swallow, and overall quality of life.